Induced defense and its cost in two bryophyte species. Issue 5 (4th May 2021) - Chen, Yong‐Da; Moles, Angela; Bu, Zhao‐Jun; Zhang, Ming‐Ming; Wang, Zu‐Cheng; Zhao, Hong‐Yan
Abstract : Premise: Current knowledge about defense strategies in plants under herbivore pressure is predominantly based on vascular plants. Bryophytes are rarely consumed by herbivores since they have ample secondary metabolites. However, it is unknown whether bryophytes have induced defenses against herbivory and whether there is a trade‐off between growth and defense in bryophytes. Methods: In an experiment with two peatland bryophytes, Sphagnum magellanicum Brid. and S . fuscum (Schimp.) H. Klinggr., two kinds of herbivory, clipping with scissors and grazing by mealworms ( Tenebrio molitor L.) were simulated. At the end of the experiment, we measured growth traits, carbon‐based defense compounds (total phenolics and cellulose) and storage compounds (total nonstructural carbohydrates) of these two Sphagnum species. Results: Grazing but not clipping increased total phenolics and C:N ratio and reduced biomass production and height increment. A negative relationship between biomass production and total phenolics was found in S . magellanicum but not in S . fuscum, indicating a growth–defense trade‐off that is species‐specific. Grazing reduced the sugar starch content of S . magellanicum and the sugar of S . fuscum . Either clipping or grazing had no effect on chlorophyll fluorescence (including actual and maximum photochemical efficiency of photosystem II) except that a significant effect of clipping on actual photochemical efficiency in S . fuscum was observed. Conclusions: Our results suggest that Sphagnum can have induced defense against herbivory and that this defense can come at a cost of growth. These findings advance our knowledge about induced defense in bryophytes, the earliest land plants.